The Impact of Memorable Halal Travel Experience - SUMARYADI, SUMARYADI; HURRIYATI, Ratih; WIBOWO, Lili Adi; GAFFAR, Vanessa (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
The objective of this research was verifying the hypothesis that a memorable halal travel experience had an effect on future travel intention in halal tourism. This quantitative research was conducted by asking Muslim foreign tourists who were visiting Indonesia about their perceptions of halal tourism directly using a questionnaire. The results showed the structural equation modelling analysis verified that memorable halal travel experience contributed to increasing future travel intention. The practical implications of this research showed that it was important to create a unique and memorable travel experience in strengthening the attractiveness and competitiveness of halal destinations.